Inclusive soteriology of Aswaja theology: An analysis of Jauharah al-Tawhid and its implications for intra-religious dialogue - Haq, Akiq Zainul; Huriani, Yeni; Kuswana, Dadang; Dollah, Hajjah Sri Rahayu Nurjanah binti Haji (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to extract the inclusive soteriological formulation of Aswaja from the text Jauharah al-Tawhid and the tradition of syarh, assess its implications for the design of intra-Islamic dialogue, and develop operational tools in the form of SOPs, checklists, rubrics, and facilitation protocols that are publicly accountable. The study uses a two-track qualitative approach. The text track is carried out through a close hermeneutic reading of ibarat-syarh by mapping usul/furu and the status of dalil (qat’i/zanni). The application track involves interviews and FGDs with facilitators, kiai, and community activists. Data were analyzed using Reflexive Thematic Analysis, supplemented by source-method-researcher triangulation, member-checking, audit trail, and a Delphi-based consensus test. The research findings formulate five principles of Aswaja's inclusive soteriology: firmness in proposals (qathi), openness in furu (zanni), rejection of takfir (contempt) against sinners, tawaqquf (religious tolerance) in the face of inconclusive evidence, and recognition of the udhr bil-jahl (the evil-doer) and ahl al-fatrah (the people of fatrah) as soteriological variables. These principles are mapped into dialogue SOPs in the form of issue classification, freezing of khilafiyyat (the wrong-doer), reason-giving procedures, tawaqquf (the wrong-doer), restorative language, the udzr bil-jahl protocol, and official clarification channels. The findings can be applied in the Religious Moderation program, the framework for Islamic intra-faith dialogue, the design of community-based conflict prevention policies, curriculum development in Islamic universities, and mediator training. These results are useful for Islamic boarding schools (pesantren), government institutions, interfaith organizations, and community facilitators in promoting tolerance and reducing sectarian tensions. This research introduces a two-track Delphi-based model that weaves classical texts into a community policy framework, as an example of